Human Leucocyte Antigen-G (HLA-G) and Its Murine Functional Homolog Qa2 in the Trypanosoma cruzi Infection - Fabrício C. Dias; Celso T. Mendes-Junior; Maria C. Silva; Fabrine S. M. Tristão; Renata Dellalibera-Joviliano; Philippe Moreau; Edson G. Soares; Jean G. Menezes; André Schmidt; Roberto O. Dantas; José A. Marin-Neto; João S. Silva; et al. (Hindawi Limited, 2015)
Genetic susceptibility factors, parasite strain, and an adequate modulation of the immune system seem to be crucial for disease progression after Trypanosoma cruzi infection. HLA-G and its murine functional homolog Qa2 have well-recognized immunomodulatory properties. We evaluated the HLA-G 3' untranslated region (3'UTR) polymorphic sites (associated with mRNA stability and target for microRNA binding) and HLA-G tissue expression (heart, colon, and esophagus) in patients presenting Chagas disease, stratified according to the major clinical variants. Further, we investigated the transcriptional levels of Qa2 and other pro- and anti-inflammatory genes in affected mouse tissues during T. cruzi experimental acute and early chronic infection induced by the CL strain. Chagas disease patients exhibited differential HLA-G 3'UTR susceptibility allele/genotype/haplotype patterns, according to the major clinical variant (digestive/cardiac/mixed/indeterminate). HLA-G constitutive expression on cardiac muscle and colonic cells was decreased in Chagasic tissues; however, no difference was observed for Chagasic and non-Chagasic esophagus tissues. The transcriptional levels of Qa2 and other anti and proinflammatory (CTLA-4, PDCD1, IL-10, INF-γ, and NOS-2) genes were induced only during the acute T. cruzi infection in BALB/c and C57BL/6 mice. We present several lines of evidence indicating the role of immunomodulatory genes and molecules in human and experimental T. cruzi infection.